Dreams of iron and steel : - Cadbury, Deborah (Fourth Estate, 2004)
A world that had changed little from the Middle Ages was altered beyond recognition by the engineering genius of the nineteenth century: rivers tamed, oceans pacified, continents bridged. In Dreams of Iron and Steel, acclaimed historian Deborah Cadbury tells the heroic tale of the visionaries and ordinary workers who brought to life seven wonders of engineering that still have the power to awe and inspire us today. From the London sewers that banished cholera to the Panama Canal that shaved thousands of miles off a dangerous sea passage, from the Hoover Dam that diverted the world's most unpredictable river to give power to over half of the country to the transcontinental railroad that fulfilled the dream of manifest destiny. Dreams of iron and steel reveals the epic struggles and personal fortunes and reputations were lost and won.